Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels